Binder composition for power storage device, slurry for power storage device electrode, power storage device electrode, and power storage device
The binder composition for power storage devices, featuring a polymer with specific repeating units, addresses the adhesion issues with active materials that undergo large volume changes, resulting in improved flexibility, adhesion, and durability of power storage device electrodes.
Patent Information
- Application Number
- JP2021542775
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-29
- Filing Date
- 2020-08-18
- Publication Date
- 2025-04-07
- Estimated Expiration
- 2040-08-18
AI Technical Summary
Existing electrode binders fail to maintain sufficient adhesion with active materials that undergo large volume changes due to lithium storage and release, leading to decreased capacity and durability in power storage devices.
A binder composition for power storage devices comprising a polymer (A) with specific repeating units derived from conjugated diene compounds, aromatic vinyl compounds, and unsaturated carboxylic acids, which improves flexibility and adhesion, and is used in a slurry with an active material like silicon to enhance charging and discharging durability.
The binder composition significantly improves the flexibility and adhesion of power storage device electrodes, leading to enhanced charging and discharging durability, even with active materials that exhibit large volume changes.
Smart Images

Figure 0007657719000001 
Figure 0007657719000002 
Figure 0007657719000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a binder composition for an electricity storage device, a slurry for an electricity storage device electrode, an electricity storage device electrode, and an electricity storage device. [Background technology]
[0002] In recent years, there has been a demand for power storage devices having high voltage and high energy density as power sources for driving electronic devices. Lithium ion batteries and lithium ion capacitors are expected to be such power storage devices.
[0003] The electrodes used in such electricity storage devices are produced by applying a composition (slurry for electricity storage device electrodes) containing an active material and a polymer that functions as a binder to the surface of a current collector and drying it. The properties required of the polymer used as a binder include the ability to bind active materials together and the ability to adhere to the current collector, abrasion resistance in the process of winding up the electrode, and resistance to powdering so that fine powder of the active material does not fall off from the applied and dried composition coating film (hereinafter also referred to as the "active material layer") even when cut afterwards.
[0004] It has been empirically demonstrated that the binding ability between the active materials, the adhesion ability between the active material and the current collector, and the resistance to powder falling off are almost proportional to the performance, and therefore, in the present specification, these may be collectively referred to as "adhesion".
[0005] In recent years, in order to achieve higher output and higher energy density of power storage devices, the use of materials with large lithium storage capacities as active materials has been studied. For example, as disclosed in Patent Document 1, a method of utilizing silicon materials with a theoretical lithium storage capacity of up to about 4,200 mAh / g as active materials is considered promising.
[0006] However, active materials using such materials with large lithium occlusion capacity undergo large volume changes due to the absorption and release of lithium, and therefore, when conventional electrode binders are applied to such materials with large lithium occlusion capacity, the adhesiveness cannot be maintained and the active material peels off, resulting in a significant capacity loss during charging and discharging.
[0007] As a technique for improving the adhesion of electrode binders, a technique for controlling the amount of surface acid of particulate binder particles (see Patent Documents 2 and 3) and a technique for improving the above-mentioned properties by using a binder having an epoxy group or a hydroxyl group (see Patent Documents 4 and 5) have been proposed. In addition, a technique for binding an active material with a rigid molecular structure of polyimide to suppress the volume change of the active material (see Patent Document 6) has been proposed. In addition, a technique for using a water-soluble polymer such as polyacrylic acid (see Patent Document 7) has also been proposed. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2004-185810 A [Patent Document 2] International Publication No. 2011 / 096463 [Patent Document 3] International Publication No. 2013 / 191080 [Patent Document 4] JP 2010-205722 A [Patent Document 5] JP 2010-3703 A [Patent Document 6] JP 2011-204592 A [Patent Document 7] International Publication No. 2015 / 098050 Summary of the Invention [Problem to be solved by the invention]
[0009] However, the electrode binders disclosed in the above Patent Documents 1 to 7 do not have sufficient adhesion for practical use of new active materials, such as silicon materials, which have a large lithium occlusion capacity and a large volume change associated with the occlusion and release of lithium. When such electrode binders are used, the active material falls off due to repeated charging and discharging, causing the electrode to deteriorate, and there is a problem that the durability required for practical use cannot be sufficiently obtained.
[0010] Thus, some aspects of the present invention provide a binder composition for an electricity storage device that can produce an electricity storage device electrode that is excellent in flexibility and adhesion and also exhibits good charge / discharge durability characteristics. Some aspects of the present invention also provide a slurry for an electricity storage device electrode that contains the composition. Some aspects of the present invention also provide an electricity storage device electrode that is excellent in flexibility and adhesion and also exhibits good charge / discharge durability characteristics. Still further, some aspects of the present invention provide an electricity storage device that has excellent charge / discharge durability characteristics. [Means for solving the problem]
[0011] The present invention has been made to solve at least part of the above-mentioned problems, and can be realized in any of the following aspects.
[0012] One embodiment of the binder composition for an electrical storage device according to the present invention is Contains a polymer (A) and a liquid medium (B), When the total amount of repeating units contained in the polymer (A) is 100 parts by mass, the polymer (A) 20 to 60 parts by mass of a repeating unit (a1) derived from a conjugated diene compound; 35 to 75 parts by mass of a repeating unit (a2) derived from an aromatic vinyl compound; and 1 to 10 parts by mass of a repeating unit (a3) derived from an unsaturated carboxylic acid, The weight average molecular weight of the THF soluble component of the polymer (A) is 100,000 to 600,000.
[0013] In one embodiment of the binder composition for an electricity storage device, The surface tension at a solid concentration of 40% and a temperature of 25°C may be 45 to 60 mN / m.
[0014] In any one of the embodiments of the binder composition for an electricity storage device, The THF gel of the polymer (A) may be 60 to 99%.
[0015] In any one of the embodiments of the binder composition for an electricity storage device, The polymer (A) is a polymer particle, The number average particle size of the polymer particles may be 50 nm or more and 500 nm or less.
[0016] In any one of the embodiments of the binder composition for an electricity storage device, The liquid medium (B) may be water.
[0017] One embodiment of a slurry for an electric storage device electrode according to the present invention is The binder composition for an electricity storage device according to any one of the above aspects and an active material are contained therein.
[0018] In one embodiment of the slurry for an electricity storage device electrode, The active material may contain a silicon material.
[0019] One aspect of the electricity storage device electrode according to the present invention is The electrode assembly includes a current collector and an active material layer formed by applying the slurry for an electricity storage device electrode according to any one of the above aspects onto a surface of the current collector and drying the applied active material layer.
[0020] One aspect of the electricity storage device according to the present invention is The power storage device includes the electrode according to the above aspect. Effect of the Invention
[0021] The binder composition for an electric storage device according to the present invention can improve flexibility and adhesion, and therefore can produce an electric storage device electrode that exhibits good charge / discharge durability characteristics. The binder composition for an electric storage device according to the present invention exerts the above-mentioned effect particularly when the electric storage device electrode contains a material with a large lithium occlusion capacity as an active material, for example, a carbon material such as graphite or a silicon material. In this way, a material with a large lithium occlusion capacity can be used as the active material of the electric storage device electrode, and therefore the battery performance is also improved. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Preferred embodiments of the present invention will be described in detail below. Note that the present invention is not limited to the embodiments described below, and should be understood to include various modified examples that are implemented within the scope of the present invention.
[0023] In this specification, the term "(meth)acrylic acid" encompasses both "acrylic acid" and "methacrylic acid". Similarly, the term "(meth)acrylate" encompasses both "acrylate" and "methacrylate". Similarly, the term "(meth)acrylamide" encompasses both "acrylamide" and "methacrylamide".
[0024] In this specification, a numerical range described as "X to Y" is interpreted as including the numerical value X as the lower limit and including the numerical value Y as the upper limit.
[0025] 1. Binder composition for power storage devices The binder composition for an electrical storage device according to one embodiment of the present invention contains a polymer (A) and a liquid medium (B). The polymer (A) contains 20 to 60 parts by mass of a repeating unit (a1) derived from a conjugated diene compound, 35 to 75 parts by mass of a repeating unit (a2) derived from an aromatic vinyl compound, and 1 to 10 parts by mass of a repeating unit (a3) derived from an unsaturated carboxylic acid, where the total amount of repeating units contained in the polymer (A) is 100 parts by mass. The weight average molecular weight of the THF-soluble component of the polymer (A) is 100,000 to 600,000.
[0026] The binder composition for an electricity storage device according to this embodiment can be used as a material for producing an electrode for an electricity storage device (active material layer) having improved bonding ability between active materials, improved adhesion ability between an active material and a current collector, and improved resistance to powder falling off, and can also be used as a material for forming a protective film for suppressing a short circuit caused by dendrites that occur during charging and discharging. Each component contained in the binder composition for an electricity storage device according to this embodiment will be described in detail below.
[0027] 1.1. Polymer (A) The binder composition for an electricity storage device according to this embodiment contains a polymer (A). The polymer (A) contains, when the total amount of repeating units contained in the polymer (A) is taken as 100 parts by mass, 20 to 60 parts by mass of a repeating unit (a1) (hereinafter also simply referred to as "repeating unit (a1)") derived from a conjugated diene compound, 35 to 75 parts by mass of a repeating unit (a2) (hereinafter also simply referred to as "repeating unit (a2)") derived from an aromatic vinyl compound, and 1 to 10 parts by mass of a repeating unit (a3) (hereinafter also simply referred to as "repeating unit (a3)") derived from an unsaturated carboxylic acid. In addition to the repeating units, the polymer (A) may contain a repeating unit derived from another monomer copolymerizable therewith.
[0028] The polymer (A) contained in the binder composition for a storage battery device according to this embodiment may be in a latex form dispersed in the liquid medium (B) or may be dissolved in the liquid medium (B), but is preferably in a latex form dispersed in the liquid medium (B). When the polymer (A) is in a latex form dispersed in the liquid medium (B), the stability of a slurry for a storage battery device electrode (hereinafter, also simply referred to as "slurry") prepared by mixing the polymer (A) with an active material is improved, and the coating property of the slurry on a current collector is also improved, which is preferable.
[0029] Hereinafter, the repeating units constituting the polymer (A), the physical properties of the polymer (A), and the production method will be described in that order.
[0030] 1.1.1. Repeating units constituting polymer (A) 1.1.1.1. Repeating units derived from conjugated diene compounds (a1) The content of the repeating unit (a1) derived from a conjugated diene compound is 20 to 60 parts by mass when the total of the repeating units contained in the polymer (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a1) is preferably 23 parts by mass, more preferably 25 parts by mass. The upper limit of the content of the repeating unit (a1) is preferably 57 parts by mass, more preferably 55 parts by mass. When the polymer (A) contains the repeating unit (a1) in the above range, the dispersibility of the active material and the filler is improved, and a uniform active material layer and a protective film can be prepared, so that the structural defects of the electrode plate are eliminated and good charge and discharge characteristics are exhibited. In addition, the polymer (A) covering the surface of the active material can be given elasticity, and the polymer (A) can be stretched to improve adhesion, so that good charge and discharge durability characteristics are exhibited.
[0031] The conjugated diene compound is not particularly limited, but examples thereof include 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, etc., and one or more selected from these can be used. Among these, 1,3-butadiene is particularly preferred.
[0032] 1.1.1.2. Repeating units (a2) derived from aromatic vinyl compounds The content of the repeating unit (a2) derived from an aromatic vinyl compound is 35 to 75 parts by mass when the total amount of the repeating units contained in the polymer (A) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (a2) is preferably 38 parts by mass, and more preferably 40 parts by mass. The upper limit of the content of the repeating unit (a2) is preferably 72 parts by mass, and more preferably 70 parts by mass. By containing the repeating unit (a2) in the above range, the polymer (A) has an appropriate binding strength with respect to graphite used as an active material, and an electricity storage device electrode having excellent flexibility and adhesion can be obtained.
[0033] The aromatic vinyl compound is not particularly limited, but examples thereof include styrene, α-methylstyrene, p-methylstyrene, vinyltoluene, chlorostyrene, divinylbenzene, and the like, and one or more selected from these can be used.
[0034] 1.1.1.3. Repeating units derived from unsaturated carboxylic acids (a3) The content of the repeating unit (a3) derived from an unsaturated carboxylic acid is 1 to 10 parts by mass when the total of the repeating units contained in the polymer (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a3) is preferably 2 parts by mass, more preferably 3 parts by mass. The upper limit of the content of the repeating unit (a3) is preferably 9 parts by mass, more preferably 8 parts by mass. When the polymer (A) contains the repeating unit (a3) in the above range, the dispersibility of the active material and the filler is improved. In addition, the affinity with the silicon material as the active material is improved, and the swelling of the silicon material is suppressed, thereby exhibiting good charge / discharge durability characteristics.
[0035] The unsaturated carboxylic acid is not particularly limited, but may be one or more selected from monocarboxylic acids and dicarboxylic acids (including anhydrides) such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, fumaric acid, itaconic acid, etc. The unsaturated carboxylic acid may be one or more selected from acrylic acid, methacrylic acid, itaconic acid, etc.
[0036] 1.1.1.4. Other repeating units In addition to the repeating units (a1) to (a3), the polymer (A) may contain repeating units derived from other monomers copolymerizable therewith. Examples of such repeating units include a repeating unit (a4) derived from an unsaturated carboxylic acid ester (hereinafter also simply referred to as "repeating unit (a4)"), a repeating unit (a5) derived from a (meth)acrylamide (hereinafter also simply referred to as "repeating unit (a5)"), a repeating unit (a6) derived from an α,β-unsaturated nitrile compound (hereinafter also simply referred to as "repeating unit (a6)"), a repeating unit (a7) derived from a compound having a sulfonic acid group (hereinafter also simply referred to as "repeating unit (a7)"), and a repeating unit derived from a cationic monomer.
[0037] <Repeating Unit (a4) Derived from Unsaturated Carboxylic Acid Ester> The polymer (A) may contain a repeating unit (a4) derived from an unsaturated carboxylic acid ester. The content of the repeating unit (a4) is preferably 0 to 15 parts by mass when the total of the repeating units contained in the polymer (A) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (a4) is preferably 1 part by mass, more preferably 2 parts by mass. The upper limit of the content of the repeating unit (a4) is preferably 12 parts by mass, more preferably 10 parts by mass. When the polymer (A) contains the repeating unit (a4) in the above range, the affinity between the polymer (A) and the electrolyte is improved, and an increase in internal resistance due to the binder becoming an electric resistance component in the electricity storage device is suppressed, and a decrease in adhesion due to excessive absorption of the electrolyte may be prevented.
[0038] Among the unsaturated carboxylic acid esters, (meth)acrylic acid esters can be preferably used. Specific examples of (meth)acrylic acid esters include, for example, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, n-amyl (meth)acrylate, isoamyl (meth)acrylate, hexyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol di(meth)acrylate, tri( ...propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, tri(meth)acrylate, propylene glycol di(meth)acrylate, Examples of the acrylate include trimethylolpropane acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, allyl (meth)acrylate, 2-hydroxymethyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 5-hydroxypentyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, glycerin mono(meth)acrylate, and glycerin di(meth)acrylate, and one or more selected from these can be used. Among these, one or more selected from methyl (meth)acrylate, ethyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and methyl (meth)acrylate is particularly preferred.
[0039] <Repeating unit (a5) derived from (meth)acrylamide> The polymer (A) may contain a repeating unit (a5) derived from (meth)acrylamide. The content of the repeating unit (a5) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (A) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (a5) is preferably 1 part by mass, more preferably 2 parts by mass. The upper limit of the content of the repeating unit (a5) is preferably 8 parts by mass, more preferably 5 parts by mass. When the polymer (A) contains the repeating unit (a5) in the above range, the dispersibility of the active material and the filler in the slurry may be improved. In addition, the flexibility of the obtained active material layer may become appropriate, and the adhesion between the current collector and the active material layer may be improved. Furthermore, since the bonding ability between the active materials containing a carbon material such as graphite and a silicon material can be increased, an active material layer having better flexibility and adhesion to the current collector may be obtained.
[0040] Examples of (meth)acrylamides include, but are not limited to, acrylamide, methacrylamide, N-isopropylacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N,N-diethylacrylamide, N,N-diethylmethacrylamide, N,N-dimethylaminopropylacrylamide, N,N-dimethylaminopropylmethacrylamide, N-methylolmethacrylamide, N-methylolacrylamide, diacetoneacrylamide, maleic acid amide, and acrylamide tert-butylsulfonic acid, and one or more selected from these can be used.
[0041] <Repeating unit (a6) derived from an α,β-unsaturated nitrile compound> The polymer (A) may contain a repeating unit (a6) derived from an α,β-unsaturated nitrile compound. The content of the repeating unit (a6) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (A) is taken as 100 parts by mass. The lower limit of the content of the repeating unit (a6) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (a6) is preferably 8 parts by mass, more preferably 5 parts by mass. When the polymer (A) contains the repeating unit (a6) in the above range, it is possible to reduce the dissolution of the polymer (A) in the electrolyte solution, and the decrease in adhesion due to the electrolyte solution may be suppressed. In addition, the increase in internal resistance caused by the polymer component dissolved in the electricity storage device becoming an electric resistance component may be suppressed.
[0042] The α,β-unsaturated nitrile compound is not particularly limited, and examples thereof include acrylonitrile, methacrylonitrile, α-chloroacrylonitrile, α-ethylacrylonitrile, vinylidene cyanide, etc., and one or more selected from these can be used. Among these, one or more selected from the group consisting of acrylonitrile and methacrylonitrile are preferred, and acrylonitrile is particularly preferred.
[0043] <Repeating Unit (a7) Derived from a Compound Having a Sulfonic Acid Group> The polymer (A) may contain a repeating unit (a7) derived from a compound having a sulfonic acid group. The content of the repeating unit (a7) is preferably 0 to 10 parts by mass when the total of the repeating units contained in the polymer (A) is 100 parts by mass. The lower limit of the content of the repeating unit (a7) is preferably 0.5 parts by mass, more preferably 1 part by mass. The upper limit of the content of the repeating unit (a7) is preferably 8 parts by mass, more preferably 5 parts by mass.
[0044] The compound having a sulfonic acid group is not particularly limited, but examples thereof include compounds having a sulfonic acid group such as vinyl sulfonic acid, styrene sulfonic acid, allyl sulfonic acid, sulfoethyl (meth)acrylate, sulfopropyl (meth)acrylate, sulfobutyl (meth)acrylate, 2-acrylamido-2-methylpropanesulfonic acid, 2-hydroxy-3-acrylamidopropanesulfonic acid, and 3-allyloxy-2-hydroxypropanesulfonic acid, as well as alkali salts thereof, and one or more selected from these can be used.
[0045] <Repeating units derived from cationic monomers> The polymer (A) may contain repeating units derived from a cationic monomer. The cationic monomer is not particularly limited, but is preferably at least one monomer selected from the group consisting of secondary amine (salt), tertiary amine (salt), and quaternary ammonium salt. Specific examples of these cationic monomers are not particularly limited, but include 2-(dimethylamino)ethyl (meth)acrylate, methyl 4-quaternary salt of dimethylaminoethyl (meth)acrylate chloride, 2-(diethylamino)ethyl (meth)acrylate, 3-(dimethylamino)propyl (meth)acrylate, 3-(diethylamino)propyl (meth)acrylate, 4-(dimethylamino)phenyl (meth)acrylate, 2-[(3,5-dimethylpyrazolyl)carbonylamino]ethyl (meth)acrylate, 2-(0-[1'-methylpropylideneamino]carboxamido)ethyl (meth)acrylate, 2-(1-aziridinyl)ethyl (meth)acrylate, methacryloylcholine chloride, tris(2-acryloyloxyethyl) isocyanurate, 2-vinylpyridine, quinacridine red, 1,2-di(2-pyridyl)ethylene, 4'-hydrazino-2-stilbazoles dihydrochloride hydrate, 4-(4-dimethylaminostyryl)quinoline, 1-vinylimidazole, diallylamine, diallylamine hydrochloride, triallylamine, diallyldimethylammonium chloride, dichloramide, N-allylbenzylamine, N-allylaniline, 2,4-diamino-6-diallylamino-1,3,5-triazine, N-trans-cinnamyl-N-methyl-(1-naphthylmethyl)amine hydrochloride, trans-N-(6,6-dimethyl-2-hepten-4-ynyl)-N-methyl-1-naphthylmethylamine hydrochloride, and the like. These monomers may be used alone or in combination of two or more.
[0046] 1.1.2. Physical properties of the polymer (A) <Weight average molecular weight of the THF-soluble component> The weight average molecular weight of the THF (tetrahydrofuran) soluble component of the polymer (A) is 100,000 to 600,000. The lower limit of the weight average molecular weight of the THF soluble component of the polymer (A) is preferably 110,000, more preferably 120,000. The upper limit of the weight average molecular weight of the THF soluble component of the polymer (A) is preferably 550,000, more preferably 500,000. The weight average molecular weight of the THF soluble component can be measured using the method described in the examples of this specification.
[0047] It is generally known that in the early stages of polymerization, the repeating units described above react mainly in a linear fashion, and the polymerized linear polymers crosslink with each other in the later stages of polymerization. On the other hand, it is difficult to directly measure the molecular weight of one crosslinked polymer chain in a polymer, but it can be assumed that the molecular weights of the crosslinked polymer chain and the polymer chains that have not reached crosslinking are close to each other. This polymer chain that has not been used for crosslinking is easily soluble in organic solvents, and can be analyzed by measuring the weight average molecular weight of the component dissolved in THF. Therefore, the weight average molecular weight of the polymer component dissolved in THF can be indirectly replaced by the weight average molecular weight of the crosslinked polymer chain in the polymer.
[0048] The higher the molecular weight of the crosslinked polymer in the polymer, the longer the polymer chain between the crosslinks, which means that the distance between the crosslinking points of the polymer is longer. If the distance between the crosslinking points is longer, the polymer will be easier to expand and contract when the active material swells and shrinks, and the polymer chain will not be cut, making it easier to maintain the structure of the polymer. It is also assumed that the flexibility of the polymer will be higher. If the weight average molecular weight of the THF-soluble component of the polymer (A) is 100,000 or more, the structure maintenance and flexibility of the polymer (A) will be high, which is preferable. If the weight average molecular weight of the THF-soluble component of the polymer (A) is 600,000 or less, the polymer (A) will not become too hard, and the adhesion to the active material and the current collector will be improved, which is preferable. Therefore, if the weight average molecular weight of the THF-soluble component of the polymer (A) is 100,000 to 600,000, it is assumed that the polymer will easily follow the swelling and shrinkage of the active material when the charge and discharge cycle is performed, resulting in good results.
[0049] <THFゲル> In this specification, the THF gel of polymer (A) is defined as the area ratio (%) of the weight average molecular weight of 1,000,000 or more in an integrated molecular weight distribution curve obtained by gel permeation chromatography (GPC).
[0050] The THF gel of the polymer (A) is preferably 60 to 99%, more preferably 65 to 98%. When the THF gel of the polymer (A) is 60% or more, the polymer structure can be maintained in the electrolyte, and the electrode structure can also be maintained during repeated charging and discharging, which is preferable. When the THF gel is 99% or less, the polymer does not become too hard, and the adhesion to the active material and the current collector is improved, which is preferable. Therefore, when the THF gel of the polymer (A) is 60 to 99%, it is assumed that the polymer can easily follow the swelling and shrinkage of the active material during charge and discharge cycles, resulting in good results.
[0051] <Surface tension> The surface tension of the binder composition for an electricity storage device, measured under conditions of a solid content of 40% and a temperature of 25° C., is preferably 45 to 60 mN / m, more preferably 47 to 58 mN / m, and particularly preferably 48 to 56 mN / m. The surface tension of the polymer can be measured by the method described in the examples of this specification.
[0052] When the surface tension value of the binder composition for an electricity storage device measured under the above conditions is within the above range, it indicates that the surface of the polymer (A) is highly hydrophobic. As a result, when the slurry for an electricity storage device electrode is applied to a current collector, migration of the polymer (A) is suppressed and the polymer (A) is uniformly adsorbed onto the active material, which may result in good adhesion between active materials and between the current collector and the active material.
[0053] <Number average particle diameter> When the polymer (A) is a particle, the number average particle size of the particles is preferably 50 nm or more and 500 nm or less, more preferably 60 nm or more and 450 nm or less, and particularly preferably 70 nm or more and 400 nm or less. When the number average particle size of the particles of the polymer (A) is within the above range, the particles of the polymer (A) are easily adsorbed on the surface of the active material, so that the particles of the polymer (A) can move along with the movement of the active material. As a result, migration can be suppressed, and the deterioration of electrical properties can be reduced in some cases.
[0054] The number average particle size of the polymer (A) particles can be calculated from the average particle size of 50 particles obtained from images of the particles observed with a transmission electron microscope (TEM). Examples of the transmission electron microscope include "H-7650" manufactured by Hitachi High-Technologies Corporation.
[0055] 1.1.3. Method for producing polymer (A) The method for producing the polymer (A) is not particularly limited, but may be, for example, an emulsion polymerization method carried out in the presence of a known emulsifier (surfactant), chain transfer agent, polymerization initiator, etc. As the emulsifier (surfactant), chain transfer agent, and polymerization initiator, compounds described in Japanese Patent No. 5999399 and the like can be used.
[0056] The emulsion polymerization method for synthesizing the polymer (A) may be carried out in a single-stage polymerization or in a multi-stage polymerization of two or more stages.
[0057] When the synthesis of polymer (A) is carried out by single-stage polymerization, the mixture of the above-mentioned monomers can be subjected to emulsion polymerization in the presence of a suitable emulsifier, chain transfer agent, polymerization initiator, etc., preferably at 40 to 80°C, preferably for 4 to 36 hours.
[0058] When the synthesis of the polymer (A) is carried out by two-stage polymerization, it is preferable to set the polymerization in each stage as follows.
[0059] The proportion of the monomer used in the first-stage polymerization is preferably in the range of 20 to 100% by mass, more preferably in the range of 25 to 100% by mass, based on the total mass of the monomers (the sum of the mass of the monomers used in the first-stage polymerization and the mass of the monomers used in the second-stage polymerization). By carrying out the first-stage polymerization at such a proportion of the monomers, it is possible to obtain particles of the polymer (A) that are excellent in dispersion stability and are unlikely to cause agglomerates, and it is also preferable that the increase in viscosity over time of the binder composition for an electrical storage device is suppressed.
[0060] The types and proportions of monomers used in the second-stage polymerization may be the same as or different from the types and proportions of monomers used in the first-stage polymerization.
[0061] From the viewpoint of the dispersibility of the particles of the resulting polymer (A), the polymerization conditions in each stage are preferably as follows. First-stage polymerization: a temperature of preferably 40 to 80° C.; a polymerization time of preferably 2 to 36 hours; a polymerization conversion rate of preferably 50% by mass or more, more preferably 60% by mass or more. Second stage polymerization; a temperature preferably between 40 and 80°C; a polymerization time preferably between 2 and 18 hours.
[0062] By controlling the total solids concentration in the emulsion polymerization to 50% by mass or less, the polymerization reaction can be carried out in a state in which the dispersion stability of the particles of the obtained polymer (A) is good. This total solids concentration is preferably 48% by mass or less, and more preferably 45% by mass or less.
[0063] Whether the synthesis of the polymer (A) is carried out as a one-stage polymerization or a two-stage polymerization method, it is preferable to add a neutralizing agent to the polymerization mixture after the emulsion polymerization is completed to adjust the pH to about 5 to 10, preferably 6 to 9.5, and more preferably 6.5 to 9. The neutralizing agent used here is not particularly limited, but examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide; ammonia, etc. By setting the pH in the above range, the stability of the polymer (A) is improved. By concentrating the polymerization mixture after the neutralization treatment, the solid content concentration can be increased while maintaining the good stability of the polymer (A).
[0064] 1.1.4. Content of polymer (A) The content of the polymer (A) in the binder composition for an electricity storage device according to this embodiment is preferably 10 to 100 parts by mass, more preferably 20 to 95 parts by mass, and particularly preferably 25 to 90 parts by mass, in 100 parts by mass of the polymer component. Here, the polymer component includes the polymer (A), a polymer other than the polymer (A) described below, a thickener, and the like.
[0065] 1.2. Liquid medium (B) The binder composition for an electric storage device according to this embodiment contains a liquid medium (B). The liquid medium (B) is preferably an aqueous medium containing water, and more preferably water. The aqueous medium can contain a non-aqueous medium other than water. Examples of the non-aqueous medium include amide compounds, hydrocarbons, alcohols, ketones, esters, amine compounds, lactones, sulfoxides, and sulfone compounds, and one or more selected from these can be used. The binder composition for an electric storage device according to this embodiment uses an aqueous medium as the liquid medium (B), which reduces the degree of adverse effects on the environment and increases the safety for workers who handle the binder composition.
[0066] The content of the non-aqueous medium in the aqueous medium is preferably 10 parts by mass or less, more preferably 5 parts by mass or less, and particularly preferably substantially free, per 100 parts by mass of the aqueous medium. Here, "substantially free" means that the non-aqueous medium is not intentionally added as a liquid medium, and may include a non-aqueous medium that is inevitably mixed in when preparing the binder composition for an electrical storage device.
[0067] 1.3.Other Additives The binder composition for an electrical storage device according to this embodiment may contain additives other than the above-mentioned components as necessary. Examples of such additives include polymers other than the polymer (A), preservatives, thickeners, etc.
[0068] <Polymers other than polymer (A)> The binder composition for a storage battery device according to the present embodiment may contain a polymer other than the polymer (A). Such a polymer is not particularly limited, but may be an acrylic polymer containing an unsaturated carboxylic acid ester or a derivative thereof as a structural unit, or a fluorine-based polymer such as PVDF (polyvinylidene fluoride). These polymers may be used alone or in combination of two or more. By containing these polymers, flexibility and adhesion may be further improved.
[0069] <Preservatives> The binder composition for a storage battery device according to the present embodiment may contain a preservative. By containing a preservative, it may be possible to suppress the proliferation of bacteria, mold, and the like and the generation of foreign matter when the binder composition for a storage battery device is stored. Specific examples of the preservative include compounds described in Japanese Patent No. 5477610 and the like.
[0070] <Thickener> The binder composition for an electricity storage device according to this embodiment may contain a thickener. By containing a thickener, it may be possible to further improve the coatability of the slurry and the charge / discharge characteristics of the resulting electricity storage device.
[0071] Specific examples of thickeners include cellulose compounds such as carboxymethylcellulose, methylcellulose, and hydroxypropylcellulose; poly(meth)acrylic acid; ammonium salts or alkali metal salts of the cellulose compounds or the poly(meth)acrylic acid; polyvinyl alcohol (co)polymers such as polyvinyl alcohol, modified polyvinyl alcohol, and ethylene-vinyl alcohol copolymers; and water-soluble polymers such as saponified copolymers of unsaturated carboxylic acids such as (meth)acrylic acid, maleic acid, and fumaric acid with vinyl esters. Among these, alkali metal salts of carboxymethylcellulose and alkali metal salts of poly(meth)acrylic acid are preferred.
[0072] Examples of commercially available thickeners include alkali metal salts of carboxymethylcellulose such as CMC1120, CMC1150, CMC2200, CMC2280, and CMC2450 (all manufactured by Daicel Corporation).
[0073] When the binder composition for an electrical storage device according to this embodiment contains a thickener, the content of the thickener is preferably 5 parts by mass or less, and more preferably 0.1 to 3 parts by mass, relative to 100 parts by mass of the total solid content of the binder composition for an electrical storage device.
[0074] 1.4. pH of the binder composition for an electricity storage device The pH of the binder composition for an electricity storage device according to this embodiment is preferably 5 to 10, more preferably 6 to 9.5, and particularly preferably 6.5 to 9. When the pH is within this range, problems such as insufficient leveling and dripping can be suppressed, and it becomes easy to produce an electricity storage device electrode that has both good electrical properties and good adhesion.
[0075] In this specification, "pH" refers to a physical property measured as follows: It is a value measured at 25°C using a pH meter using a glass electrode calibrated with a neutral phosphate standard solution and a borate standard solution as pH standard solutions, in accordance with JIS Z8802:2011. Examples of such pH meters include "HM-7J" manufactured by DKK-TOA Corporation and "D-51" manufactured by HORIBA, LTD.
[0076] It should be noted that the pH of the binder composition for an electricity storage device is not determined solely by the monomer composition, although it is not denied that the pH is affected by the monomer composition constituting the polymer (A). In other words, it is generally known that the pH of a binder composition for an electricity storage device changes depending on the polymerization conditions, etc., even if the monomer composition is the same, and the examples in the present specification merely show one example.
[0077] For example, even with the same monomer composition, the amount of carboxy groups derived from the unsaturated carboxylic acid exposed on the surface of the resulting polymer differs between the case where all the unsaturated carboxylic acid is added to the polymerization reaction solution from the beginning and then other monomers are added sequentially, and the case where monomers other than the unsaturated carboxylic acid are added to the polymerization reaction solution and the unsaturated carboxylic acid is added last. In this way, it is believed that the pH of the binder composition for electrical storage devices will be significantly different just by changing the order in which the monomers are added in the polymerization method.
[0078] 2. Slurry for electricity storage devices The slurry for an electric storage device according to one embodiment of the present invention contains the above-mentioned binder composition for an electric storage device. The above-mentioned binder composition for an electric storage device can be used as a material for producing a protective film for suppressing a short circuit caused by dendrites that occur with charging and discharging, and can also be used as a material for producing an electrode (active material layer) for an electric storage device having improved binding ability between active materials, adhesion ability between an active material and a current collector, and resistance to powder falling. Therefore, the slurry for an electric storage device for producing a protective film (hereinafter also referred to as "slurry for a protective film") and the slurry for an electric storage device for forming an active material layer of an electrode for an electric storage device (hereinafter also referred to as "slurry for an electric storage device electrode") will be described separately.
[0079] 2.1.Slurry for protective film "Slurry for protective film" refers to a dispersion liquid used to prepare a protective film on the surface of an electrode or a separator, or both, by applying the slurry to the surface of an electrode or a separator, or both, and then drying the slurry. The slurry for protective film according to this embodiment may be composed only of the binder composition for a storage battery device described above, or may further contain an inorganic filler. Each component contained in the slurry for protective film according to this embodiment will be described in detail below. Note that the binder composition for a storage battery device is as described above, so description thereof will be omitted.
[0080] 2.1.1. Inorganic fillers The slurry for the protective film according to the present embodiment contains an inorganic filler, thereby improving the toughness of the protective film. As the inorganic filler, it is preferable to use at least one type of particle selected from the group consisting of silica, titanium oxide (titania), aluminum oxide (alumina), zirconium oxide (zirconia), and magnesium oxide (magnesia). Among these, titanium oxide or aluminum oxide is preferable from the viewpoint of further improving the toughness of the protective film. Moreover, as the titanium oxide, rutile type titanium oxide is more preferable.
[0081] The average particle size of the inorganic filler is preferably 1 μm or less, and more preferably 0.1 to 0.8 μm. The average particle size of the inorganic filler is preferably larger than the average pore size of the separator, which is a porous membrane. This reduces damage to the separator and prevents the inorganic filler from clogging the micropores of the separator.
[0082] The slurry for the protective film according to the present embodiment preferably contains 0.1 to 20 parts by mass, more preferably 1 to 10 parts by mass, of the binder composition for an electrical storage device, calculated as solid content, per 100 parts by mass of the inorganic filler. When the content ratio of the binder composition for an electrical storage device is within the above range, a good balance between the toughness of the protective film and the permeability of lithium ions is achieved, and as a result, the resistance increase rate of the obtained electrical storage device can be further reduced.
[0083] 2.1.2. Liquid media A liquid medium may be added to the slurry for the protective film according to this embodiment in addition to the amount carried over from the binder composition for the electrical storage device. The amount of the liquid medium added can be adjusted as necessary so as to obtain an optimal slurry viscosity depending on the coating method, etc. Examples of such a liquid medium include the materials described in "1.2. Liquid medium (B)" above.
[0084] 2.1.3.Other Ingredients The slurry for the protective film according to this embodiment may contain the materials described above in "1.3. Other additives" in appropriate amounts as necessary.
[0085] 2.2. Slurry for electricity storage device electrodes The "slurry for an electric storage device electrode" refers to a dispersion liquid used for forming an active material layer on the surface of a current collector by applying the dispersion liquid to the surface of the current collector and then drying the same. The slurry for an electric storage device electrode according to this embodiment contains the above-mentioned binder composition for an electric storage device and an active material.
[0086] Generally, a slurry for an electric storage device electrode often contains a binder component such as an SBR copolymer and a thickener such as carboxymethyl cellulose in order to improve adhesion. On the other hand, the slurry for an electric storage device electrode according to this embodiment can improve flexibility and adhesion even when it contains only the above-mentioned polymer (A) as a polymer component. Of course, the slurry for an electric storage device electrode according to this embodiment may contain a polymer other than the polymer (A) or a thickener in order to further improve adhesion.
[0087] Hereinafter, the components contained in the slurry for an electricity storage device electrode according to this embodiment will be described.
[0088] 2.2.1. Polymer (A) The composition, physical properties, production method, etc. of the polymer (A) are as described above, so description thereof will be omitted.
[0089] The content of the polymer component in the slurry for an electric storage device electrode according to this embodiment is preferably 1 to 8 parts by mass, more preferably 1 to 7 parts by mass, and particularly preferably 1.5 to 6 parts by mass, relative to 100 parts by mass of the active material. When the content of the polymer component is within the above range, the dispersibility of the active material in the slurry is good, and the coating property of the slurry is also excellent. Here, the polymer component includes the polymer (A), a polymer other than the polymer (A) that is added as necessary, a thickener, etc.
[0090] 2.2.2.Active material Examples of active materials used in the slurry for the power storage device electrode according to this embodiment include carbon materials, silicon materials, oxides containing lithium atoms, lead compounds, tin compounds, arsenic compounds, antimony compounds, aluminum compounds, conductive polymers such as polyacene, A X B Y O Z(wherein A is an alkali metal or a transition metal, B is at least one selected from transition metals such as cobalt, nickel, aluminum, tin, and manganese, O is an oxygen atom, and X, Y, and Z are numbers within the ranges of 1.10>X>0.05, 4.00>Y>0.85, and 5.00>Z>1.5, respectively.) and other metal oxides. Specific examples of these include compounds described in Japanese Patent No. 5999399.
[0091] The electricity storage device electrode slurry according to this embodiment can be used when producing either a positive electrode or a negative electrode of an electricity storage device, and is preferably used for both a positive electrode and a negative electrode.
[0092] When lithium iron phosphate is used as a positive electrode active material, there are problems such as insufficient charge / discharge characteristics and poor adhesion. Lithium iron phosphate has a fine primary particle size and is known to be in the form of secondary aggregates. When the particles are repeatedly charged and discharged, the aggregates break down in the active material layer, causing separation of the active materials, leading to peeling from the current collector and disruption of the conductive network inside the active material layer.
[0093] However, in the case of an electricity storage device electrode produced using the electricity storage device electrode slurry according to this embodiment, the above-mentioned problems do not occur even when lithium iron phosphate is used, and good electrical properties can be exhibited. This is thought to be because the polymer (A) can firmly bind the lithium iron phosphate and at the same time, can maintain the state in which the lithium iron phosphate is firmly bound even during charging and discharging.
[0094] On the other hand, when preparing a negative electrode, among the active materials exemplified above, it is preferable to use one containing a silicon material.Since the amount of lithium absorbed per unit weight of a silicon material is larger than that of other active materials, the silicon material is contained as a negative electrode active material, so that the storage capacity of the obtained power storage device can be increased, and as a result, the output and energy density of the power storage device can be increased.
[0095] In addition, the negative electrode active material is preferably a mixture of a silicon material and a carbon material. Since the volume change of the carbon material accompanying charge and discharge is smaller than that of the silicon material, the use of the mixture of the silicon material and the carbon material as the negative electrode active material can mitigate the effect of the volume change of the silicon material, and can further improve the adhesion ability between the active material layer and the current collector.
[0096] When silicon (Si) is used as an active material, while it has a high capacity, it undergoes a large volume change when it absorbs lithium. This causes silicon materials to pulverize due to repeated expansion and contraction, which can cause them to peel off from the current collector and separate from each other, and can easily disrupt the conductive network inside the active material layer. This property causes the charge / discharge durability of the energy storage device to deteriorate drastically in a short period of time.
[0097] However, the electricity storage device electrode produced using the electricity storage device electrode slurry according to this embodiment can exhibit good electrical properties even when a silicon material is used without the above-mentioned problems. This is thought to be because the polymer (A) can firmly bind the silicon material, and at the same time, even if the silicon material expands in volume by absorbing lithium, the polymer (A) expands and contracts, thereby maintaining the state in which the silicon material is firmly bound.
[0098] The content of the silicon material in 100% by mass of the active material is preferably 1% by mass or more, more preferably 1 to 50% by mass, even more preferably 5 to 45% by mass, and particularly preferably 10 to 40% by mass. When the content of the silicon material in 100% by mass of the active material is within the above range, an electricity storage device having an excellent balance between improved output and energy density of the electricity storage device and charge / discharge durability characteristics can be obtained.
[0099] The active material is preferably in the form of particles. The average particle diameter of the active material is preferably 0.1 to 100 μm, and more preferably 1 to 20 μm. Here, the average particle diameter of the active material refers to the volume average particle diameter calculated from the particle size distribution measured using a particle size distribution measuring device that uses a laser diffraction method as the measurement principle. Examples of such laser diffraction type particle size distribution measuring devices include the HORIBA LA-300 series and the HORIBA LA-920 series (both manufactured by Horiba, Ltd.).
[0100] 2.2.3.Other ingredients In addition to the above-mentioned components, other components may be added to the slurry for the power storage device electrode according to this embodiment, if necessary. Examples of such components include polymers other than the polymer (A), thickeners, liquid media, conductive agents, pH adjusters, corrosion inhibitors, cellulose fibers, etc. The polymers other than the polymer (A) and thickeners may be selected from the compounds exemplified in "1.3. Other Additives" above, and may be used for the same purpose and in the same content ratio.
[0101] <Liquid medium> A liquid medium may be further added to the slurry for an electric storage device electrode according to this embodiment in addition to the liquid medium carried over from the binder composition for an electric storage device. The liquid medium added may be the same as or different from the liquid medium (B) contained in the binder composition for an electric storage device, but is preferably selected from the liquid media exemplified in "1.2. Liquid medium (B)" above.
[0102] The content of the liquid medium (including the amount carried over from the binder composition for an electricity storage device) in the slurry for an electricity storage device electrode according to this embodiment is preferably such that the solids concentration in the slurry (meaning the proportion of the total mass of the components in the slurry other than the liquid medium to the total mass of the slurry; the same applies below) is 30 to 70 mass%, and more preferably 40 to 60 mass%.
[0103] <Conductive agent> In the slurry for a power storage device electrode according to this embodiment, a conductive agent may be further added for the purpose of imparting conductivity and buffering the volume change of the active material due to the ingress and egress of lithium ions.
[0104] Specific examples of the conductive agent include carbons such as activated carbon, acetylene black, ketjen black, furnace black, graphite, carbon fiber, and fullerene. Among these, acetylene black or ketjen black can be preferably used. The content ratio of the conductive agent is preferably 20 parts by mass or less, more preferably 1 to 15 parts by mass, and particularly preferably 2 to 10 parts by mass with respect to 100 parts by mass of the active material.
[0105] <pH adjuster and corrosion inhibitor> In the slurry for a power storage device electrode according to this embodiment, a pH adjuster and / or a corrosion inhibitor may be further added for the purpose of suppressing the corrosion of the current collector according to the type of the active material.
[0106] Examples of the pH adjuster include hydrochloric acid, phosphoric acid, sulfuric acid, acetic acid, formic acid, ammonium phosphate, ammonium sulfate, ammonium acetate, ammonium formate, ammonium chloride, sodium hydroxide, potassium hydroxide, etc. Among these, sulfuric acid, ammonium sulfate, sodium hydroxide, and potassium hydroxide are preferable. It can also be selected and used from among the neutralizing agents described in the method for producing the polymer (A).
[0107] Examples of the corrosion inhibitor include ammonium metavanadate, sodium metavanadate, potassium metavanadate, ammonium metatungstate, sodium metatungstate, potassium metatungstate, ammonium paratungstate, sodium paratungstate, potassium paratungstate, ammonium molybdate, sodium molybdate, potassium molybdate, and the like. Among these, ammonium paratungstate, ammonium metavanadate, sodium metavanadate, potassium metavanadate, and ammonium molybdate are preferred.
[0108] <Cellulose fiber> Cellulose fibers may be further added to the slurry for an electricity storage device electrode according to this embodiment. The addition of cellulose fibers may improve the adhesion of the active material to the current collector. It is believed that the fibrous cellulose fibers bond adjacent active materials together in a fibrous form by linear adhesion or linear contact, thereby preventing the active material from falling off and improving the adhesion to the current collector.
[0109] The average fiber length of the cellulose fiber can be selected from a wide range of 0.1 to 1000 μm, and is, for example, preferably 1 to 750 μm, more preferably 1.3 to 500 μm, further preferably 1.4 to 250 μm, and particularly preferably 1.8 to 25 μm. When the average fiber length is within the above range, the surface smoothness (coating film uniformity) becomes good, and the adhesion of the active material to the current collector may be improved.
[0110] The fiber length of the cellulose fibers may be uniform, and the coefficient of variation of the fiber length ([standard deviation of fiber length / average fiber length]×100) is, for example, preferably 0.1 to 100, more preferably 0.5 to 50, and particularly preferably 1 to 30. The maximum fiber length of the cellulose fibers is, for example, preferably 500 μm or less, more preferably 300 μm or less, even more preferably 200 μm or less, even more preferably 100 μm or less, and particularly preferably 50 μm or less.
[0111] It is advantageous to set the average fiber length of the cellulose fibers to 5 times or less the average thickness of the active material layer, since this further improves the surface smoothness (uniformity of the coating film) and the adhesion of the active material to the current collector. The average fiber length of the cellulose fibers is preferably 0.01 to 5 times, more preferably 0.02 to 3 times, and particularly preferably 0.03 to 2 times the average thickness of the active material layer.
[0112] The average fiber diameter of the cellulose fibers is preferably 1 nm to 10 μm, more preferably 5 nm to 2.5 μm, further preferably 20 nm to 700 nm, and particularly preferably 30 nm to 200 nm. When the average fiber diameter is within the above range, the volume occupied by the fibers does not become too large, and the packing density of the active material may be increased. Therefore, the cellulose fibers are preferably cellulose nanofibers having an average fiber diameter of nanometer size (for example, cellulose nanofibers having an average fiber diameter of about 10 nm to 500 nm, preferably about 25 nm to 250 nm).
[0113] The fiber diameter of the cellulose fibers is also uniform, and the variation coefficient of the fiber diameter ([standard deviation of fiber diameter / average fiber diameter]×100) is preferably 1 to 80, more preferably 5 to 60, and particularly preferably 10 to 50. The maximum fiber diameter of the cellulose fibers is preferably 30 μm or less, more preferably 5 μm or less, and particularly preferably 1 μm or less.
[0114] The ratio of the average fiber length to the average fiber diameter of the cellulose fibers (aspect ratio) is, for example, preferably 10 to 5000, more preferably 20 to 3000, and particularly preferably 50 to 2000. When the aspect ratio is within the above range, the adhesion of the active material to the current collector is good, and the surface smoothness (coating uniformity) of the electrode may be good without weakening the breaking strength of the fibers.
[0115] In the present invention, the average fiber length, the standard deviation of the fiber length distribution, the maximum fiber length, the average fiber diameter, the standard deviation of the fiber diameter distribution, and the maximum fiber diameter may be values calculated from fibers (n=about 20) measured based on electron micrographs.
[0116] The material of the cellulose fiber may be formed of a polysaccharide having a β-1,4-glucan structure. Examples of the cellulose fiber include cellulose fibers derived from higher plants (e.g., natural cellulose fibers (pulp fibers) such as wood fibers (wood pulp of conifers, broad-leaved trees, etc.), bamboo fibers, sugarcane fibers, seed hair fibers (e.g., cotton linters, bombax cotton, kapok, etc.), gin bark fibers (e.g., hemp, paper mulberry, Mitsumata, etc.), and leaf fibers (e.g., Manila hemp, New Zealand hemp, etc.)), cellulose fibers derived from animals (e.g., sea squirt cellulose, etc.), cellulose fibers derived from bacteria (e.g., cellulose contained in nata de coco, etc.), chemically synthesized cellulose fibers (e.g., rayon, cellulose esters (cellulose acetate, etc.), cellulose ethers (e.g., cellulose derivatives such as hydroxyalkyl celluloses such as hydroxyethyl cellulose (HEC) and hydroxypropyl cellulose, and alkyl celluloses such as methyl cellulose and ethyl cellulose, etc.). These cellulose fibers may be used alone or in combination of two or more types.
[0117] Among these cellulose fibers, cellulose fibers derived from higher plants, for example, cellulose fibers derived from pulp such as wood fibers (such as wood pulp from conifers, broad-leaved trees, etc.) and seed hair fibers (such as cotton linter pulp), are preferred because they are easy to prepare into nanofibers with an appropriate aspect ratio.
[0118] The method for producing cellulose fiber is not particularly limited, and depending on the desired fiber length and fiber diameter, conventional methods such as those described in JP-B-60-19921, JP-A-2011-26760, JP-A-2012-25833, JP-A-2012-36517, JP-A-2012-36518, and JP-A-2014-181421 may be used.
[0119] 2.2.4. Method for preparing slurry for power storage device electrodes The slurry for the electric storage device electrode according to the present embodiment may be produced by any method as long as it contains the above-mentioned binder composition for the electric storage device and the active material. From the viewpoint of producing a slurry having better dispersibility and stability more efficiently and inexpensively, it is preferable to produce the slurry by adding the active material and optional additive components used as necessary to the binder composition for the electric storage device and mixing them. Specific examples of the production method include the method described in Japanese Patent No. 5999399 and the like.
[0120] 3.Electricity storage device electrodes An electric storage device electrode according to one embodiment of the present invention comprises a current collector and an active material layer formed by applying and drying the above-mentioned slurry for an electric storage device electrode on the surface of the current collector. Such an electric storage device electrode can be produced by applying the above-mentioned slurry for an electric storage device electrode to the surface of a current collector such as a metal foil to form a coating film, and then drying the coating film to form an active material layer. The electric storage device electrode produced in this manner is formed by binding an active material layer containing the above-mentioned polymer (A) and active material, and further optional components added as necessary, on a current collector, and therefore has excellent flexibility and adhesion and exhibits good charge / discharge durability characteristics.
[0121] The current collector is not particularly limited as long as it is made of a conductive material, and examples thereof include the current collectors described in Japanese Patent No. 5999399 and the like.
[0122] In the electricity storage device electrode according to this embodiment, when a silicon material is used as the active material, the content of elemental silicon in 100 parts by mass of the active material layer is preferably 2 to 30 parts by mass, more preferably 2 to 20 parts by mass, and particularly preferably 3 to 10 parts by mass. When the content of elemental silicon in the active material layer is within the above range, the electricity storage capacity of the electricity storage device produced using it is improved, and an active material layer with a uniform distribution of elemental silicon can be obtained.
[0123] In the present invention, the content of silicon element in the active material layer can be measured by the method described in Japanese Patent No. 5,999,399, for example.
[0124] 4. Energy storage devices The electric storage device according to one embodiment of the present invention includes the above-mentioned electric storage device electrode, further contains an electrolytic solution, and can be manufactured by a conventional method using components such as a separator. A specific manufacturing method can include, for example, a method in which a negative electrode and a positive electrode are stacked with a separator interposed therebetween, and the stack is rolled or folded according to the shape of the battery to house it in a battery container, and the electrolytic solution is injected into the battery container and sealed. The shape of the battery can be any appropriate shape, such as a coin type, a cylindrical type, a square type, or a laminate type.
[0125] The electrolyte may be liquid or gel, and may be selected from among known electrolytes used in power storage devices that effectively exhibit the function of a battery depending on the type of active material. The electrolyte may be a solution in which an electrolyte is dissolved in a suitable solvent. Examples of such electrolytes and solvents include compounds described in Japanese Patent No. 5999399.
[0126] The above-mentioned electric storage device can be applied to lithium ion secondary batteries, electric double layer capacitors, lithium ion capacitors, etc., which require discharge at a high current density. Among these, lithium ion secondary batteries are particularly preferred. In the electric storage device electrode and electric storage device according to this embodiment, members other than the binder composition for electric storage devices can be known members for lithium ion secondary batteries, electric double layer capacitors, and lithium ion capacitors.
[0127] 5. Working Example The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are by mass unless otherwise specified.
[0128] 5.1. Example 1 5.1.1. Preparation of binder composition for power storage devices and evaluation of its physical properties (1) Preparation of Binder Composition for Electric Storage Device A binder composition for a storage battery device containing a polymer (A) was obtained by one-stage polymerization as shown below. A monomer mixture consisting of 400 parts by mass of water, 40 parts by mass of 1,3-butadiene, 55 parts by mass of styrene, 2 parts by mass of itaconic acid, and 3 parts by mass of acrylic acid, 0.1 parts by mass of tert-dodecyl mercaptan as a chain transfer agent, 2 parts by mass of sodium alkyl diphenyl ether disulfonate as an emulsifier, and 0.2 parts by mass of potassium persulfate as a polymerization initiator was charged into a reactor, and polymerization was carried out at 70 ° C. for 24 hours while stirring, and the reaction was terminated at a polymerization conversion rate of 98%. Unreacted monomers were removed from the particle dispersion of polymer (A) obtained in this way, and after concentration, a 10% aqueous sodium hydroxide solution and water were added to obtain a binder composition for a storage battery device containing particles of polymer (A) with a solid content concentration of 20% by mass and a pH of 8.0.
[0129] (2) Measurement of weight average molecular weight of THF-soluble components 10 mg of a binder composition for an electricity storage device having a solid content concentration of 20% by mass was mixed with 5 mL of THF, left at 25°C for 16 hours, and then passed through a 0.45 μm membrane filter to prepare a measurement sample. Next, using the measurement sample obtained under the following measurement conditions, the weight average molecular weight (Mw) of the THF-soluble component was determined in terms of polystyrene (RI detection) by gel permeation chromatography using the following column. The measurement results are shown in Table 1. [Measurement conditions] ·Temperature: 35℃ Solvent: THF ·Flow rate: 1.0mL / min ·Concentration: 0.2% by weight Measurement sample injection volume: 100μL [column] "GPC TSKgel α-2500" (30 cm x 2 tubes) manufactured by Tosoh Corporation was used. (Log between Mw 1,000 and 20,000,000) 10 (Measured under conditions where the linear correlation between Mw and elution time is 0.98 or higher.)
[0130] (3) Measurement of THF gel From the integrated molecular weight distribution curve obtained by the above gel permeation chromatography measurement, the area ratio (%) of polymer (A) having a weight average molecular weight of 1,000,000 or more was determined.
[0131] (4) Measurement of surface tension The binder composition for an electricity storage device having a solid content concentration of 20% by mass obtained above was further concentrated to obtain a binder composition for an electricity storage device having a solid content concentration of 40% by mass. The surface tension of the binder composition for an electricity storage device thus obtained was measured under the following conditions. The measurement results are shown in Table 1. (conditions) Using a digital tension meter (RTM-101, manufactured by Rigo Co., Ltd.), 25 mL of the binder composition for electricity storage devices, concentrated to a solid content concentration of 40 mass%, was weighed out onto an aluminum dish, and the aluminum dish was placed on a sample stage. After immersing a platinum ring with a center diameter of 1.9 cm and a wire diameter of 0.06 cm by 2 mm into the sample, the sample stage was lowered at 25°C, and the force applied at the moment when the film with the liquid surface broke (the force with which the liquid pulls the ring) was measured.
[0132] (5) Measurement of number average particle size A drop of the latex obtained by diluting the binder composition for a storage battery device obtained above to 0.1 wt% was dropped onto a collodion support film with a pipette, and a drop of 0.02 wt% osmium tetroxide solution was further dropped onto the collodion support film with a pipette, and the film was air-dried for 12 hours to prepare a sample. The sample thus prepared was observed at a magnification of 10K (magnification) using a transmission electron microscope (TEM, Hitachi High-Technologies Corporation, model number "H-7650"), and image analysis was performed using the HITACH EMIP program to calculate the number average particle size of 50 randomly selected particles of polymer (A). The measurement results are shown in Table 1.
[0133] (6) pH measurement The pH of the binder composition for an electricity storage device obtained above was measured at 25° C. using a pH meter (manufactured by Horiba, Ltd.), and it was confirmed to be pH 8.0.
[0134] 5.1.2. Preparation of Slurry for Electricity Storage Device Electrodes (1) Synthesis of silicon material (active material) A mixture of crushed silicon dioxide powder (average particle size 10 μm) and carbon powder (average particle size 35 μm) was heat-treated for 10 hours in an electric furnace with the temperature adjusted to the range of 1100°C to 1600°C under a nitrogen gas flow (0.5 NL / min) to obtain a powder with the composition formula SiO x A silicon oxide powder (average particle size 8 μm) represented by (x=0.5-1.1) was obtained. 300 g of this silicon oxide powder was charged into a batch-type heating furnace, and while maintaining a reduced pressure of 100 Pa absolute pressure by a vacuum pump, the temperature was raised from room temperature (25 ° C) to 1100 ° C at a heating rate of 300 ° C / h. Next, while maintaining the pressure in the heating furnace at 2000 Pa, methane gas was introduced at a flow rate of 0.5 NL / min, and a heat treatment (graphite coating treatment) was performed at 1100 ° C for 5 hours. After the graphite coating treatment, the powder was cooled to room temperature at a temperature drop rate of 50 ° C / h to obtain about 330 g of graphite-coated silicon oxide powder. This graphite-coated silicon oxide was a conductive powder (active material) in which the surface of silicon oxide was coated with graphite, with an average particle size of 10.5 μm. The proportion of the graphite coating was 2 mass% when the entirety of the obtained graphite-coated silicon oxide was taken as 100 mass%.
[0135] (2) Preparation of slurry for power storage device electrodes Into a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03"), 1 part by mass (solid content equivalent, added as an aqueous solution with a concentration of 2% by mass) of a thickener (product name "CMC2200", manufactured by Daicel Corporation), 4 parts by mass (solid content equivalent, added as the binder composition for a power storage device obtained above) of the polymer (A), 85.5 parts by mass (solid content equivalent) of artificial graphite (manufactured by Hitachi Chemical Co., Ltd., product name "MAG") which is highly crystalline graphite as a negative electrode active material, 9.5 parts by mass (solid content equivalent) of the graphite-coated silicon oxide powder obtained above, and 1 part by mass of carbon (manufactured by Denka Company, Ltd., acetylene black) as a conductivity imparting agent were added, and the mixture was stirred at 60 rpm for 1 hour to obtain a paste. Water was added to the obtained paste to adjust the solid concentration to 48% by mass, and then the mixture was stirred at 200 rpm for 2 minutes, at 1800 rpm for 5 minutes, and then further stirred under reduced pressure (approximately 2.5 × 10 4 The mixture was stirred and mixed at 1,800 rpm for 1.5 minutes at 10 Pa to prepare a slurry for an electricity storage device electrode (C / Si=90 / 10) containing 10 mass % of Si in the negative electrode active material.
[0136] In addition, a slurry for a storage device electrode (C / Si=100 / 0) not containing Si in the negative electrode active material was prepared in the same manner as the slurry for a storage device electrode (C / Si=90 / 10), except for adjusting the amounts of artificial graphite and graphite-coated silicon oxide powder used.
[0137] 5.1.3. Manufacturing and evaluation of energy storage devices (1) Manufacturing of electrodes (negative electrodes) for power storage devices The slurry for an electric storage device electrode (C / Si=90 / 10 or C / Si=100 / 0) obtained above was uniformly applied by a doctor blade method onto the surface of a current collector made of copper foil with a thickness of 20 μm so that the film thickness after drying would be 80 μm, and the coating was dried at 60° C. for 10 minutes and then dried at 120° C. for 10 minutes. After that, the density of the active material layer was 1.5 g / cm 3 The mixture was pressed by a roll press machine so as to obtain an electricity storage device electrode (negative electrode).
[0138] (2) Evaluation of adhesion strength of negative electrode coating layer On the surface of the electricity storage device electrode obtained above, 10 incisions were made vertically and horizontally at 2 mm intervals using a knife to a depth from the active material layer to the current collector, creating a grid pattern. An 18 mm wide adhesive tape (manufactured by Nichiban Co., Ltd., product name "Cellotape" (registered trademark), as specified in JIS Z1522) was attached to the incisions and immediately peeled off, and the degree of loss of the active material was evaluated by visual inspection. The evaluation criteria were as follows. The evaluation results are shown in Table 1. (Evaluation Criteria) 5 points: No active material layers fell off. 4 points: 1 to 5 pieces of the active material layer are missing. 3 points: 6 to 20 pieces of the active material layer have fallen off. 2 points: 21 to 40 pieces of the active material layer fell off. 1 point: 41 or more pieces of the active material layer are missing.
[0139] (3) Manufacturing the counter electrode (positive electrode) Into a two-shaft planetary mixer (manufactured by Primix Corporation, product name "TK Hivismix 2P-03"), 4 parts by mass (solid content equivalent) of electrochemical device electrode binder (manufactured by Kureha Corporation, product name "KF Polymer #1120"), 3 parts by mass of conductive assistant (manufactured by Denka Co., Ltd., product name "Denka Black 50% Pressed Product"), 100 parts by mass (solid content equivalent) of LiCoO2 (manufactured by Hayashi Chemical Co., Ltd.) with an average particle diameter of 5 μm as a positive electrode active material, and 36 parts by mass of N-methylpyrrolidone (NMP) were added and stirred at 60 rpm for 2 hours. After adding NMP to the obtained paste to adjust the solid content concentration to 65 mass%, a stirring and defoaming machine (manufactured by Thinky Corporation, product name "Awatori Rentaro") was used to stir at 200 rpm for 2 minutes, 1800 rpm for 5 minutes, and further reduced pressure (approximately 2.5 × 10 4The slurry for the positive electrode was prepared by stirring and mixing at 1800 rpm for 1.5 minutes at 1000 rpm (1 Pa). The slurry for the positive electrode was uniformly applied to the surface of a current collector made of aluminum foil by a doctor blade method so that the film thickness after solvent removal would be 80 μm, and the solvent was removed by heating at 120° C. for 20 minutes. Thereafter, the density of the active material layer was 3.0 g / cm 3 The resultant mixture was pressed by a roll press machine so as to obtain a counter electrode (positive electrode).
[0140] (4) Assembly of lithium-ion battery cells In a glove box substituted with Ar gas so that the dew point is -80°C or less, the negative electrode produced above was punched out to a diameter of 15.95 mm and placed on a two-electrode coin cell (manufactured by Hosen Co., Ltd., product name "HS Flat Cell"). Next, a separator made of a polypropylene porous film punched out to a diameter of 24 mm (manufactured by Celgard Co., Ltd., product name "Celgard #2400") was placed on the cell, and 500 μL of electrolyte was poured to prevent air from entering. The positive electrode produced above was punched out to a diameter of 16.16 mm and placed on the cell, and the exterior body of the two-electrode coin cell was sealed with screws to assemble a lithium-ion battery cell (electricity storage device). The electrolyte used here was a solution in which LiPF6 was dissolved at a concentration of 1 mol / L in a solvent of ethylene carbonate / ethyl methyl carbonate = 1 / 1 (mass ratio).
[0141] (5) Evaluation of charge / discharge cycle characteristics The energy storage device manufactured above was charged at a constant current (1.0 C) in a thermostatic chamber adjusted to 25° C., and when the voltage reached 4.2 V, charging was continued at a constant voltage (4.2 V). The charging was completed (cut-off) when the current value reached 0.01 C. Thereafter, discharging was started at a constant current (1.0 C), and the discharging was completed (cut-off) when the voltage reached 3.0 V, and the discharge capacity of the first cycle was calculated. In this manner, charging and discharging were repeated 100 times. The capacity retention rate was calculated using the following formula (2) and evaluated according to the following criteria. The evaluation results are shown in Table 1. Capacity retention rate (%) = (100th cycle discharge capacity) / (1st cycle discharge capacity) (2) (Evaluation Criteria) 5 points: Capacity retention is 95% or more. 4 points: Capacity retention is between 90% and 95%. 3 points: Capacity retention is between 85% and 90%. 2 points: Capacity retention is between 80% and 85%. 1 point: Capacity retention is between 75% and 80%. 0 points: Less than 75% capacity retention.
[0142] In the measurement conditions, "1C" refers to the current value at which a cell with a certain capacity is discharged at a constant current and the discharge is completed in 1 hour. For example, "0.1C" refers to the current value at which the discharge is completed in 10 hours, and "10C" refers to the current value at which the discharge is completed in 0.1 hour.
[0143] 5.2. Examples 2 to 12 and Comparative Examples 1 to 8 Binder compositions for electricity storage devices containing polymer particles with a solid content concentration of 20 mass % were obtained in the same manner as in the above "5.1.1. Preparation and physical property evaluation of binder compositions for electricity storage devices (1) Preparation of binder compositions for electricity storage devices", except that the type and amount of each monomer and the amount of emulsifier were as shown in Table 1 or Table 2 below, respectively, and the physical properties were evaluated.
[0144] Furthermore, slurries for electricity storage device electrodes were prepared in the same manner as in Example 1 above, except that the binder compositions for electricity storage devices prepared above were used, and electricity storage device electrodes and electricity storage devices were fabricated and evaluated in the same manner as in Example 1 above.
[0145] 5.3. Example 13 In Example 3, except that the thickener was 0.9 parts by mass of CMC (trade name "CMC2200", manufactured by Daicel Corporation) and 0.1 parts by mass of CNF (trade name "Celish KY-100G", manufactured by Daicel Corporation, fiber diameter 0.07 μm), a slurry for an electricity storage device electrode was prepared in the same manner as in Example 3, and an electricity storage device electrode and an electricity storage device were each produced and evaluated in the same manner as in Example 1. The results are shown in Table 3 below.
[0146] 5.4. Example 14 In Example 13, except that the thickener was 0.8 parts by mass of CMC (trade name "CMC2200", manufactured by Daicel Corporation) and 0.2 parts by mass of CNF (trade name "Celish KY-100G", manufactured by Daicel Corporation, fiber diameter 0.07 μm), a slurry for an electricity storage device electrode was prepared in the same manner as in Example 13, and an electricity storage device electrode and an electricity storage device were each fabricated and evaluated in the same manner as in Example 1. The results are shown in Table 3.
[0147] 5.5.Evaluation Results The polymer compositions, physical properties, and evaluation results used in Examples 1 to 14 and Comparative Examples 1 to 8 are shown in Tables 1 to 3 below.
[0148] [Table 1]
[0149] [Table 2]
[0150] [Table 3]
[0151] The abbreviations of the monomers in Tables 1 and 2 above represent the following compounds, respectively. <Conjugated diene compounds> BD: 1,3-butadiene ·CBD: 2-chloro-1,3-butadiene <Aromatic vinyl compounds> ST: Styrene ·DVB: Divinylbenzene <Unsaturated carboxylic acid> ·TA: Itaconic acid ·AA: Acrylic acid ·MAA: Methacrylic acid <Unsaturated carboxylic acid ester> MMA: Methyl methacrylate ·BA: Butyl acrylate 2EHA: 2-Ethylhexyl acrylate ·CHMA: Cyclohexyl methacrylate EDMA: Ethylene glycol dimethacrylate HEMA: 2-hydroxyethyl methacrylate ·HEA: 2-hydroxyethyl acrylate <(Meth)acrylamide> ·AAM: Acrylamide ·MAM: Methacrylamide <α,β-unsaturated nitrile compounds> ·AN: Acrylonitrile <Compounds having sulfonic acid groups> ·NASS: Sodium styrene sulfonate <Emulsifier> ·SAFAX: Sodium alkyl diphenyl ether disulfonate
[0152] As is clear from Tables 1 and 2, it was found that the slurry for an electric storage device electrode prepared using the binder composition for an electric storage device according to the present invention shown in Examples 1 to 12 can favorably bind active materials that undergo large volume changes accompanying charge and discharge, and can maintain good adhesion between the active material layer and the current collector, compared to Comparative Examples 1 to 8. As a result, despite repeated charge and discharge and repeated volume expansion and contraction of the active material, peeling of the active material layer was suppressed, and an electric storage device electrode having good charge and discharge durability characteristics was obtained. The reason for this is presumably that the polymer (A) contained in the binder composition of Examples 1 to 12 shown in Tables 1 and 2 has a longer distance between crosslinking points of the polymer compared to Comparative Examples 1 to 8, and therefore can follow the change in thickness of the active material layer due to charge and discharge, maintain the structure of the polymer, and maintain the conductive network inside the active material layer.
[0153] Furthermore, as is clear from the results of Table 3 above, it was found that the slurries for electricity storage device electrodes prepared using the binder compositions for electricity storage devices according to the present invention shown in Examples 13 and 14, even when used in combination with CNF as a thickener, were able to effectively bind active materials that undergo large volume changes during charging and discharging, and also were able to maintain good adhesion between the active material layer and the current collector.
[0154] The present invention is not limited to the above-described embodiments, and various modifications are possible. The present invention includes configurations that are substantially the same as those described in the embodiments (for example, configurations with the same functions, methods, and results, or configurations with the same purpose and effect). The present invention also includes configurations in which non-essential parts of the configurations described in the above-described embodiments are replaced with other configurations. Furthermore, the present invention also includes configurations that have the same effects as the configurations described in the above-described embodiments, or that can achieve the same purpose. Furthermore, the present invention also includes configurations in which publicly known technology is added to the configurations described in the above-described embodiments.
Claims
1. Contains a polymer (A) and a liquid medium (B), When the total amount of repeating units contained in the polymer (A) is 100 parts by mass, the polymer (A) 20 to 60 parts by mass of a repeating unit (a1) derived from a conjugated diene compound; 35 to 75 parts by mass of a repeating unit (a2) derived from an aromatic vinyl compound; and 1 to 10 parts by mass of a repeating unit (a3) derived from an unsaturated carboxylic acid, the THF-soluble component of the polymer (A) has a weight average molecular weight of less than 1 million as measured by gel permeation chromatography of 100,000 to 600,000; The THF gel of the polymer (A) is 60 to 99%; The binder composition for an electrical storage device, wherein the liquid medium (B) is water.
2. 2. The binder composition for an electrical storage device according to claim 1, having a surface tension of 45 to 60 mN / m at a solids concentration of 40% and a temperature of 25°C.
3. The polymer (A) is a polymer particle, The binder composition for an electrical storage device according to claim 1 or 2, wherein the polymer particles have a number average particle size of 50 nm or more and 500 nm or less.
4. A slurry for an electrode of an electricity storage device, comprising the binder composition for an electricity storage device according to claim 1 and an active material.
5. The slurry for an electric storage device electrode according to claim 4 , which contains a silicon material as the active material.
6. 6. An electricity storage device electrode comprising: a current collector; and an active material layer formed by applying the slurry for an electricity storage device electrode according to claim 4 or 5 onto a surface of the current collector and drying the slurry.
7. An electricity storage device comprising the electricity storage device electrode according to claim 6.
Citation Information
Patent Citations
Binder for battery, binder composition, electrode and battery
JP1997213337A
Electrode material for lithium secondary battery, electrode structural body with the electrode material, secondary battery with the electrode structure, manufacturing method of the electrode material, manufacturing method of the electrode structural body, and manufacturing method of the secondary battery
JP2004185810A
Binder composite for secondary battery electrode, slurry for secondary battery electrode, and secondary battery electrode
JP2007087881A
Binder composition, slurry for battery electrode, electrode, and lithium secondary battery
JP2010003703A
Binder for nonaqueous electrolyte secondary battery electrode
JP2010205722A